Pengembangan dan Implementasi Lembar Kerja Siswa Berbasis Problem Based Learning - Mahlianurrahman Mahlianurrahman (MODELING: Jurnal Program Studi PGMI, 2018)
This study aims to investigate the appropriateness and the effectiveness of inquiry-based natural science learning package to improve elementary school students learning outcomes. This study employed the development model by Borg & Gall. The research procedure consisted of: (1) preliminary study, (2) planning, (3) developing preliminary form of product, (4) first revision, (5) preliminary field testing, (6) second revision, (7) main field testing, (8) final product revision, and (9) dissemination. The product testing subjects were students of grade V SD Gunong Kleng. The data were collected through tests. Pretestt-posttest questions and project assessment sheet were used to measure learning outcomes. The appropriateness of learning package was analyzed through four scales converted. The effectiveness of learning package was analyzed through gain score, and percentage of improvement. The result of the study was an inquiry-based natural science learning package for the style of motion and energy topic which appropriates and could improve learning outcomes.